Effects of COVID-19 on Mental Health and Its Relationship With Death Attitudes and Coping Styles Among Hungarian, Norwegian, and Turkish Psychology Students - Oker, Kemal; Reinhardt, Melinda; Schmelowszky, Ágoston (Frontiers in Psychology, 2022)
The purpose of this study was to investigate mental effects of coronavirus disease 2019 (COVID-19) and its relationship with death attitudes and coping styles among Hungarian, Norwegian, and Turkish psychology students. A total of 388 participants from Hungary (N = 122, 31.4%), Norway (N = 96, 24.7%), and Turkey (N = 170, 43.8%) were recruited during the pandemic. The Depression, Anxiety and Stress Scale, the Impact of Event Scale-Revised, the Carver Brief COPE Inventory, and the Death Attitude Profile-Revised were used. The results indicated that escape acceptance might be the most maladaptive death attitude during COVID-19, as it was related to poorer mental health among the Hungarian, Norwegian, and Turkish psychology students. Self-blame, behavioral disengagement, self-distraction, and substance use coping styles were also related to poorer mental health, whereas positive-reframing (only among the Hungarian and Turkish participants) and humor (only among the Norwegian participants) were related to better mental health among our sample in the context of COVID-19. The findings implied that death attitudes and coping styles may differ in their efficacy among the Hungarian, Norwegian, and Turkish participants. These differences were discussed in detail in the discussion part. During the pandemic, practitioners might pay closer attention to patients with higher escape acceptance death attitude and patients who use dysfunctional coping styles. Additionally, patients can be encouraged to use techniques involving positive reframing and humor coping styles.